2019
DOI: 10.1002/ece3.5194
|View full text |Cite
|
Sign up to set email alerts
|

Responses of biomass allocation across two vegetation types to climate fluctuations in the northern Qinghai–Tibet Plateau

Abstract: The Qinghai–Tibet Plateau (QTP) is particularly sensitive to global climate change, especially to elevated temperatures, when compared with other ecosystems. However, few studies use long‐term field measurements to explore the interannual variations in plant biomass under climate fluctuations. Here, we examine the interannual variations of plant biomass within two vegetation types (alpine meadow and alpine shrub) during 2008–2017 and their relationships with climate variables. The following results were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…Thus, there is a sense of urgency to determine a suitable stocking rate in the alpine grassland for restoring degraded grassland and improving livestock production both at the local and at the landscape scale (Barcella, Filipponi, & Assini, ; Metera, Sakowski, Słoniewski, & Romanowicz, ). In this study, we found that the maximum value of BGB occurred in moderate levels of grazing disturbance (i.e., 7.5 sheep/ha), suggesting that such stocking rates may be an optimal grassland management strategy for the alpine meadow in terms of root production, especially considering the BGB almost accounts for more than 80% biomass of plants (Dai, Guo, Du, Ke, et al, ; Dai, Guo, Zhang, et al, ; Dai, Ke, et al, ), which could provide new insight for local people and policy‐makers in government. However, it should be noted that the species richness shows the lowest value in MG in spite of the BGB peaked in MG.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Thus, there is a sense of urgency to determine a suitable stocking rate in the alpine grassland for restoring degraded grassland and improving livestock production both at the local and at the landscape scale (Barcella, Filipponi, & Assini, ; Metera, Sakowski, Słoniewski, & Romanowicz, ). In this study, we found that the maximum value of BGB occurred in moderate levels of grazing disturbance (i.e., 7.5 sheep/ha), suggesting that such stocking rates may be an optimal grassland management strategy for the alpine meadow in terms of root production, especially considering the BGB almost accounts for more than 80% biomass of plants (Dai, Guo, Du, Ke, et al, ; Dai, Guo, Zhang, et al, ; Dai, Ke, et al, ), which could provide new insight for local people and policy‐makers in government. However, it should be noted that the species richness shows the lowest value in MG in spite of the BGB peaked in MG.…”
Section: Discussionmentioning
confidence: 89%
“…The region has a characteristic plateau continental monsoon climate, with a mean annual air temperature of −1.7°C, and maximum and minimum air temperatures in July (9.8°C) and January (−14.80°C), respectively. The average annual precipitation is approximately 618 mm, with almost 80% falling in the growing season (i.e., from early May to late September; Dai, Guo, Du, Ke, et al, ; Dai, Guo, Du, Zhang, et al, ; Dai, Guo, Zhang, et al, ; Dai, Ke, et al, ). The soil is classified as Mat cryo‐sod soil on the basis of the Chinese National Soil Survey and Classification System (Institute of Soil Science, CAS, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the desert ecosystem, the plant in low precipitation condition could allocate less biomass to the leaf to avoid more moisture loss via evapotranspiration and allocate more biomass to the root to obtain more moisture and soil nutrients from a greater volume of soil (Fan et al, ; Wu et al, ). However, in the alpine ecosystem with low temperature and short growth season, the nutrient content was less as the soil nutrient supplement of the alpine ecosystems is strongly determined by nutrient mineralization (Dai, Ke, Du, Zhang, et al, ; Dai, Ke, Guo, et al, ).Therefore, there may exist trade‐off between belowground organ to capture soil nutrient and aboveground organ to capture more carbon, according to the carbon is fixed by leaves and the water or mineral nutrients were absorbed by root (McConnaughay & Coleman, ); that is, the plant might choose to obtain more biomass to plant organs that associated with the acquisition of that resource at the cost of reducing the structures biomass associated with acquisition of another resource. Moreover, this evidence was supported by the seasonal dynamics of AGB and BGB in the alpine ecosystem in a previous study (Dai, Guo, Du, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although ANPP was positively related to precipitation at large scales (Sala, Parton, Joyce, & Lauenroth, ), caution should be used when considering the differences in climate conditions of individual sites. For instance, the plants in our alpine ecosystem were limited by the low temperature and short growing season (Dai, Ke, et al, ). Moreover, the soil moisture was relative abundance relatively abundant during the growing season due to the replenishment from precipitation and thawing of seasonally frozen soil (Dai et al, ).…”
Section: Discussionmentioning
confidence: 99%